Linking nursing education to job outcomes and career pathways: qualitative insights from a graduate tracer study - Ibrahim, Asiya; Shafia, Aminath; Abdul Qoyoom, Zeena; Ludin, Salizar (International Islamic University Malaysia, 2025)
Background: Nursing education aims to equip students with essential knowledge and skills. However, concerns persist regarding the readiness of graduates for clinical work. This study explores how a public university in the Maldives supports nursing training in terms of job performance and career growth. Methods: Online Focus Group Discussions (FGDs) were conducted with purposively selected Maldives National University (MNU) nursing graduates, divided into four cohorts: Group 1 (1991- 2000), Group 2 (2001-2008), Group 3 (2009-2014), and Group 4 (2015-2019) and by years in practice (0- 4, 5-9, 10-14, ≥15). In particular, each FGD consists of eight to ten participants. A semi-structured interview guide was also employed, and discussions continued until thematic saturation was reached. Subsequently, thematic analysis was performed to interpret the data. Results: Across the dataset, five interlocking themes describe how nursing education is translating into workforce capability: 1) balancing theory and practice, 2) smooth transition to practice, 3) professional growth opportunities, 4) benefits of being a nursing graduate, and 5) challenges for local graduates. Findings indicate that nursing education via a contextualized, practice-aligned curriculum supports the transition to practice, although constraints persist in career progression. Conclusion: While being a nursing graduate offers benefits such as job security and personal fulfillment, local graduates encounter challenges such as a lack of recognition and issues related to career mobility. The study highlights the need for continuous revisions of various nursing curricula to ensure that graduates are well-prepared for success in their careers.